Association of SARS-CoV-2 vaccination status with risk of influenza-like illness and loss of workdays in healthcare workers - Tamara Dörr; Joanne Lacy; Tala Ballouz; Alexia Cusini; Fabian Grässli; Sarah Haile; Emina Kocan; J. Carsten Möller; Milo A. Puhan; Matthias Schlegel; Matthias von Kietzell; Markus Rütti; et al. (Communications Medicine)
Abstract Background In the post-pandemic phase, the value of annual SARS-CoV-2 booster vaccination in healthcare-workers is unclear. In this multicentre cohort study, we sought to determine the association of SARS-CoV-2 vaccination status and other risk factors with the occurrence of influenza-like respiratory illness and workdays lost due to influenza-like respiratory illness. Methods During a period of high SARS-CoV-2 community transmission (November 2023 to May 2024), we collected weekly data on symptoms and sick day leave and used negative binomial regression to identify risk factors for these outcomes among 1745 healthcare workers. To single out the effect of the vaccine and account for potential confounding, additional inverse probability weighted analysis was performed. Results In both analyses, we show that more SARS-CoV-2 vaccinations are associated with a higher risk of influenza-like respiratory illness and workdays lost. For influenza-like respiratory illness, the association is stronger with a more recent timing of the vaccination rather than the number of vaccinations, which suggests that the effect wanes over time. In contrast, seasonal influenza vaccination is associated with a decreased risk for both outcomes. Conclusions Based on our data, we conclude that SARS-CoV-2 booster vaccination does not contribute to the protection of the healthcare workforce in a post-pandemic setting. SARS-CoV-2 vaccination may even temporarily increase the likelihood of symptomatic infection and workday loss.